English literary Studies: Including Islamic Perspectives in Pedagogy and Practice (American Journal of Islam and Society, 2015)
Proponents of the integration of Islam into English literary studiesseek, by way of presenting Islamic worldviews in relation to thelife-worlds that English texts presumably promote, to inform (Muslim)students and practitioners of the subject about possible untowardinfluences in order to help them withstand cultural captivityand lifestyle effects. This is part of the wider concept of integratingIslam into human knowledge, which functions across a broad rangeof subject areas and generally refers to a method of looking at academicdisciplines from Islamic perspectives and enlightening thereader about relevant Islamic teachings. Based on this theoreticalpremise, in this article I focus on the need for and three importantways of teaching English literature: inculcating Islamic/moral values,identifying predominant themes and ideas inherent in literarytexts and looking at them from Islamic perspectives, and reformingthe curriculum.